Development of Learning Videos for Introducing Character Values to Early Childhood - Denissa Alfiany Luhulima; Jane Grasia Akollo (Syntax Corporation Indonesia, 2022)
The impact of the COVID-19 outbreak is being felt in various fields, one of which is education in all corners of the world, including Indonesia. The educational process that was previously carried out face-to-face is required to be immediately carried out online, both the administrative process and the learning process. All levels of education starting from PAUD to tertiary institutions carry out the online learning process. The thing that then becomes an obstacle in the online learning process is that there are several levels of education in Indonesia that cannot do online learning due to limited facilities in accessing the internet in their respective areas. One of them is the level of Early Childhood Education (PAUD) in Maluku. Not all PAUD in Maluku can carry out the online learning process. The use of media as a tool in the world of education is recognized by many educational practitioners to assist the learning process. And one of the learning media that can be used online and offline is learning video. This video development research using the ASSURE model was carried out by focusing on developing learning videos for children aged 5-6 years with the choice of topics focusing on the characters of empathy, honesty and discipline. This quantitative research was conducted at 4 PAUD schools in Kairatu Village, Kairatu District, West Seram Regency, namely El-Aye Joyo PAUD, Nurul Aini PAUD, Kairatu Indah PAUD, and Falmen PAUD. The results of the validation test from experts from the results of filling out questionnaires for children and teachers obtained the results that this learning video was good and suitable for use in the learning process in PAUD.